Modified carbon fiber-resin composite material for automobiles and method for manufacturing the same

CN122978652APending Publication Date: 2026-10-27DONGGUAN HONGYI CARBON FIBER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611284486.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提供了一种汽车用改性碳纤维-树脂复合材料及其制备方法,本发明要解决的技术问题是:针对现有碳纤维/环氧树脂复合材料中碳纤维表面活性不足、纳米增强相易团聚、界面载荷传递能力有限以及阻燃组分与力学增强难以协同的问题,提供一种汽车用改性碳纤维-树脂复合材料及其制备方法

Benefits of technology

通过在碳纤维表面先构筑聚多巴胺锚定层,可在较温和条件下引入丰富的极性活性位点,为后续纳米二氧化硅和磷氮功能组分提供稳定附着基础,降低单纯强氧化处理造成纤维表面过度刻蚀的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and discloses a modified carbon fiber-resin composite material for automobiles and a preparation method thereof. The composite material is formed by compounding and solidifying a modified carbon fiber reinforcing body and a resin matrix. A polydopamine anchoring layer, an aminated nano-silicon dioxide reinforcing layer and a hexakis (4-hydroxyphenoxy) cyclotriphosphazene interface layer are sequentially constructed on the surface of the carbon fiber. The resin matrix comprises a bisphenol F type epoxy resin, methylhexahydrophthalic anhydride, 2-ethyl-4-methyl imidazole and nano-aluminum oxide. The infiltration, mechanical occlusion and interface action between the carbon fiber and the epoxy resin are improved through the multistage interface layer, and the phosphorus-nitrogen structure and the inorganic nano-phase are utilized to form a synergistic flame-retardant and thermal-stable effect. In combination with vacuum impregnation and gradient heat-pressing solidification, the interface defects and pores can be reduced, and the composite material is suitable for automobile structural parts, load-bearing parts and protective parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a modified carbon fiber-resin composite material for automobiles and its preparation method. Background Technology

[0002] With increasing demands for lightweighting, electrification, and enhanced safety in automobiles, carbon fiber reinforced resin matrix composites, due to their high specific strength, high specific modulus, fatigue resistance, and corrosion resistance, are increasingly being used in body reinforcement components, battery pack structural components, seat frames, bumper beams, doors, and underbody protection panels. Epoxy resin, with its excellent adhesion, moldability, and dimensional stability, is a commonly used thermosetting resin matrix for carbon fiber composites.

[0003] However, industrial carbon fiber surfaces are typically smooth and chemically inert, often retaining or covering the original sizing layer, limiting the wetting and interfacial chemical interactions between the fiber and epoxy resin. Under bending, impact, or cyclic loading, the interfacial region is prone to debonding, microcrack propagation, and interlaminar damage, preventing the fiber from fully exerting its reinforcing effect. While traditional strong oxidation or high-energy treatments can improve surface activity, the treatment window is narrow, and overtreatment can cause fiber surface defects and loss of bulk strength.

[0004] On the other hand, automotive composite materials, in addition to requiring high mechanical properties, also need to consider thermal stability and flame retardant safety. Directly adding inorganic nanoparticles or phosphorus-containing flame retardants to epoxy resin can easily lead to problems such as nanoparticle agglomeration, increased resin viscosity, and migration of small-molecule flame-retardant components, and may also cause localized stress concentration, affecting interfacial load transfer. Therefore, it is necessary to construct a multi-level carbon fiber interfacial structure that combines interfacial anchoring, nano-reinforcement, and phosphorus-nitrogen flame retardancy, along with appropriate resin impregnation and curing processes, to improve interfacial bonding and molding quality while minimizing damage to the carbon fiber itself. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a modified carbon fiber-resin composite material for automobiles and its preparation method. The technical problem to be solved by the present invention is: to address the problems of insufficient surface activity of carbon fiber, easy agglomeration of nano-reinforcing phase, limited interfacial load transfer capacity, and difficulty in synergistic effect between flame retardant components and mechanical reinforcement in existing carbon fiber / epoxy resin composite materials, the present invention provides a modified carbon fiber-resin composite material for automobiles and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a modified carbon fiber-resin composite material for automobiles, which is formed by composite curing of modified carbon fiber reinforcement and resin matrix, wherein the modified carbon fiber reinforcement accounts for 35-55 wt% of the total mass of the composite material, and the resin matrix accounts for 45-65 wt% of the total mass of the composite material, the two totaling 100 wt%; The modified carbon fiber reinforcement is obtained by sequentially forming a polydopamine anchoring layer, an aminated nano-silica reinforcement layer, and a phosphorus-nitrogen-containing cyclic triphosphazene interface layer on the surface of carbon fibers; based on the mass of unmodified carbon fibers, the loading of polydopamine is 0.3–1.5 wt%, the loading of aminated nano-silica is 0.5–2.5 wt%, and the loading of the phosphorus-nitrogen-containing cyclic triphosphazene compound is 0.3–1.8 wt%; the phosphorus-nitrogen-containing cyclic triphosphazene compound is hexa(4-hydroxyphenoxy)cyclic triphosphazene; Polydopamine contains active groups such as catechol groups and amino / imine groups, which can form an adhesive anchoring layer through dopamine oxidation self-polymerization under weakly alkaline conditions; aminated nano-silica can stabilize the load through hydrogen bonding, electrostatic interaction and multi-point interaction with the surface active groups of polydopamine, while improving the surface roughness; hexa(4-hydroxyphenoxy)cyclotriphosphazene contains a phosphorus-nitrogen skeleton and multiple phenolic hydroxyl groups, which can form hydrogen bonds and multi-point interfacial interactions with the aforementioned interface layer, and exert a phosphorus-nitrogen synergistic flame retardant effect under thermal action.

[0007] The resin matrix is ​​composed of the following raw materials in parts by weight: 45-60 parts of bisphenol F type epoxy resin, 30-45 parts of methyl hexahydrophthalic anhydride, 0.3-1.0 parts of 2-ethyl-4-methylimidazolium, and 1-2 parts of nano-alumina.

[0008] Furthermore, the carbon fiber is PAN-based carbon fiber with a single filament diameter of 5-8 μm; before the interface modification, the carbon fiber is extracted with acetone for 4-8 hours to remove the original sizing agent, then treated with a nitric acid solution with a mass concentration of 5-15% at 40-60°C for 20-60 minutes, then washed with deionized water until neutral, and then vacuum dried at 60-80°C for 4-8 hours.

[0009] Further, the polydopamine anchoring layer is formed by the following method: pretreated carbon fibers are added to a dopamine hydrochloride solution with a concentration of 1.0–3.0 mg / mL, wherein the dopamine hydrochloride solution is prepared with a Tris buffer solution with a concentration of 10–50 mmol / L and the pH value is adjusted to 8.2–8.8. The mixture is stirred and reacted at 20–30°C in an air atmosphere for 6–18 h to allow dopamine to oxidize and polymerize in situ on the carbon fiber surface. After the reaction is completed, the carbon fibers are washed with deionized water and vacuum dried at 50–70°C to obtain polydopamine-modified carbon fibers.

[0010] Further, the aminated nano-silica is prepared using tetraethyl orthosilicate and 3-aminopropyltriethoxysilane, wherein the molar ratio of tetraethyl orthosilicate to 3-aminopropyltriethoxysilane is 1:0.08-0.20; specifically, tetraethyl orthosilicate is added to a mixed solvent composed of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 4-8:1. Ammonia is added to adjust the pH of the system to 9.5-11.5. After stirring and reacting at 25-40°C for 1-3 hours, 3-aminopropyltriethoxysilane is added, and the reaction continues for 3-6 hours. After centrifugation, washing with ethanol, and vacuum drying at 50-70°C, aminated nano-silica with an average particle size of 20-80 nm is obtained.

[0011] Further, the phosphorus-containing nitrogen-containing triphosphazene compound is prepared by the following method: hexachlorocyclotriphosphazene, hydroquinone, and an acid-binding agent are added to an organic solvent, wherein the molar ratio of hexachlorocyclotriphosphazene to hydroquinone is 1:6.3-7.2, and the molar ratio of hexachlorocyclotriphosphazene to the acid-binding agent is 1:6.5-8.0; the reaction is carried out under nitrogen protection at 60-80°C for 8-16 hours; after the reaction is completed, the solid salt is removed by filtration, most of the solvent is removed by vacuum, the concentrated solution is added to deionized water to precipitate the solid, washed with water, and dried under vacuum at 50-70°C to obtain hexa(4-hydroxyphenoxy)cyclotriphosphazene; the acid-binding agent is potassium carbonate, and the organic solvent is N,N-dimethylformamide.

[0012] Further, the modified carbon fiber reinforcement is prepared by the following method: polydopamine-modified carbon fiber is added to an aminated nano-silica ethanol dispersion with a concentration of 2-10 mg / mL, stirred at 25-40°C for 2-6 h, washed and dried, and then added to a hexa(4-hydroxyphenoxy)cyclotriphosphazene ethanol / tetrahydrofuran mixed solution with a concentration of 5-8 mg / mL, and assembled at 30-50°C for 2-8 h, wherein the volume ratio of ethanol to tetrahydrofuran is 1:1 to 4:1. After washing and drying, the modified carbon fiber reinforcement is obtained.

[0013] Furthermore, it includes the following steps: S1. Desizing and oxidation pretreatment are performed on the carbon fiber to form a polydopamine anchoring layer on the surface of the carbon fiber, thereby obtaining polydopamine modified carbon fiber. S2. Aminated nano-silica is loaded onto the surface of the polydopamine-modified carbon fiber, and then hexa(4-hydroxyphenoxy)cyclotriphosphazene is loaded to obtain the modified carbon fiber reinforcement. S3. Weigh 45-60 parts of bisphenol F type epoxy resin and 1-2 parts of nano alumina according to the weight ratio, disperse them at 1000-2000 r / min for 20-40 min at 60-80℃, cool them to 40-55℃, add 30-45 parts of methylhexahydrophthalic anhydride and 0.3-1.0 parts of 2-ethyl-4-methylimidazolium, stir evenly, and then degas under vacuum for 10-30 min to obtain the resin matrix; S4. Vacuum impregnate the modified carbon fiber reinforcement obtained in step S2 with the resin matrix obtained in step S3, so that the modified carbon fiber reinforcement accounts for 35-55 wt% of the total mass of the composite material, the resin matrix accounts for 45-65 wt%, and the two together are 100 wt%, to obtain a prepreg. S5. After the prepreg is laid up, it is hot-pressed and cured, cooled and demolded to obtain a modified carbon fiber-resin composite material for automobiles.

[0014] Further, in step S4, the impregnation temperature is 45-65℃, the vacuum degree is -0.085--0.098MPa, and the impregnation time is 20-60min; the resin content in the prepreg is 45-65wt%.

[0015] Furthermore, step S5 employs a gradient hot-press curing process, specifically: first, pre-pressing at 80–100℃ and 0.5–1.5MPa for 20–40 min, then curing at 120–140℃ and 2–4MPa for 1–2 h, and then curing at 155–175℃ and 3–6MPa for 2–4 h; after curing, cooling to below 60℃ at a rate of 1–3℃ / min before demolding.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: By first constructing a polydopamine anchoring layer on the carbon fiber surface, abundant polar active sites can be introduced under milder conditions, providing a stable adhesion basis for subsequent nano-silica and phosphorus-nitrogen functional components, and reducing the risk of excessive etching of the fiber surface caused by simple strong oxidation treatment.

[0017] Aminated nano-silica forms a nanoscale rough structure on the surface of polydopamine, which can increase the effective contact area between carbon fibers and epoxy resin, and improve the transfer of load from the resin matrix to carbon fibers through mechanical interlocking, hydrogen bonding and multi-point interfacial interaction; its surface amination can also improve the stability of nanoparticles at the interface and reduce the tendency of agglomeration caused by directly adding nano-silica to the resin.

[0018] Hexa(4-hydroxyphenoxy)cyclotriphosphazene is positioned and constructed in the interface region of carbon fiber. Its phosphorus and nitrogen skeleton can promote char formation when heated and play a synergistic flame retardant role in the gas phase / condensed phase. It forms an inorganic barrier with silica and nano alumina, which is beneficial to take into account flame retardancy, heat resistance and interface reinforcement.

[0019] Vacuum impregnation combined with gradient hot pressing curing can reduce air bubbles and interlayer pores in the resin system, allowing the resin to fully impregnate the carbon fiber at a lower viscosity stage, and then gradually increase the degree of curing and crosslinking density, thereby reducing internal stress and interface defects caused by rapid curing and improving the molding stability of automotive composite materials. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] The PAN-based carbon fiber used is TORAYCA™ T700SC-12K-50C type carbon fiber, manufactured by Toray Industries, Inc.; dopamine hydrochloride is Sigma-Aldrich H8502 type product with a purity ≥98%; Tris is Sigma-Aldrich 252859 type product with a purity ≥99.8%; tetraethyl orthosilicate is Sigma-Aldrich 131903 type product with a purity of 98%; 3-aminopropyltriethoxysilane is Sigma-Aldrich 440140 type product with a purity of 99%; and hexachlorocyclotriphosphazene is Sigma-Aldrich 230286 type product with a purity of 99%.

[0022] Example 1: S1. Carbon fiber pretreatment and preparation of polydopamine anchoring layer: PAN-based carbon fibers were taken and subjected to continuous extraction with acetone for 4 hours to remove the original sizing agent. After removal, the acetone was evaporated. The carbon fibers were then immersed in a 5% nitric acid solution and treated at 40°C for 20 minutes. They were repeatedly washed with deionized water until the pH of the washing solution was close to neutral, and then vacuum dried at 60°C for 4 hours. A 10 mmol / L Tris buffer solution was prepared and the pH was adjusted to 8.2. Dopamine hydrochloride was added to prepare a 1.0 mg / mL solution. The pretreated carbon fibers were added at a liquid-to-solid ratio of 15 mL / g and stirred at 20°C in air for 6 hours. After removal, the carbon fibers were washed with deionized water and vacuum dried at 50°C to constant weight, with the polydopamine loading controlled at 0.3 wt%.

[0023] S2. Preparation of Aminated Nano-Silica: 20.83 g (0.100 mol) of tetraethyl orthosilicate, 400 mL of anhydrous ethanol, and 100 mL of deionized water were added to a reaction vessel. Ammonia was added to adjust the pH to 9.5, and the mixture was stirred at 25 °C for 1 h. Then, 1.77 g (0.008 mol) of 3-aminopropyltriethoxysilane was added, and the reaction was continued for 3 h. The reaction solution was centrifuged, and the resulting solid was washed three times with ethanol and dried under vacuum at 50 °C to obtain aminated nano-silica with an average particle size of approximately 20–30 nm.

[0024] Preparation of S3, hexachlorocyclotriphosphazene: 6.95 g (0.020 mol) hexachlorocyclotriphosphazene, 13.87 g (0.126 mol) hydroquinone, 17.97 g (0.130 mol) potassium carbonate, and 300 mL N,N-dimethylformamide were added to a reaction flask equipped with nitrogen protection, stirring, and condensation. The mixture was heated to 60 °C and reacted for 8 h under nitrogen protection. After the reaction was complete, the mixture was cooled and filtered to remove the solid salt. The filtrate was concentrated under reduced pressure to approximately 1 / 4 of its original volume. The concentrate was slowly added to 800 mL of deionized water to precipitate the solid. The solid was filtered and washed three times with deionized water, then dried under vacuum at 50 °C to obtain hexachlorocyclotriphosphazene.

[0025] S4. Preparation of modified carbon fiber reinforcement: The aminated nano-silica obtained in step S2 was ultrasonically dispersed in ethanol to prepare a 2 mg / mL dispersion. The polydopamine-modified carbon fiber obtained in step S1 was added at a liquid-to-solid ratio of 20 mL / g. The mixture was stirred at 25 °C for 2 h, washed with ethanol, and vacuum dried at 50 °C, with the aminated nano-silica loading controlled at 0.5 wt%. Hexa(4-hydroxyphenoxy)cyclotriphosphazene was then dissolved in a mixed solvent of ethanol / tetrahydrofuran at a volume ratio of 1:1 to prepare a 5 mg / mL solution. The carbon fiber was added at a liquid-to-solid ratio of 20 mL / g, treated at 30 °C for 2 h, washed with ethanol, and vacuum dried at 50 °C, with the hexa(4-hydroxyphenoxy)cyclotriphosphazene loading controlled at 0.3 wt%, to obtain the modified carbon fiber reinforcement.

[0026] S5. Preparation of Resin Matrix and Composite Material: 45 parts by weight of bisphenol F epoxy resin and 1 part by weight of nano-alumina were dispersed at 60℃ and 1000 r / min for 20 min. After cooling to 40℃, 30 parts by weight of methylhexahydrophthalic anhydride and 0.3 parts by weight of 2-ethyl-4-methylimidazolium were added, stirred for 10 min, and vacuum degassed for 10 min to obtain the resin matrix. A prepreg was obtained by vacuum impregnation at 45℃ and -0.085 MPa for 20 min at a ratio of 35 wt% modified carbon fiber reinforcement and 65 wt% resin matrix. The prepreg was laid in the designed direction, pre-pressed at 80℃ and 0.5 MPa for 20 min, heated to 120℃ and cured at 2 MPa for 1 h, then heated to 155℃ and cured at 3 MPa for 2 h. The temperature was then lowered to below 60℃ at 1℃ / min, and the composite material was demolded.

[0027] Example 2: S1. PAN-based carbon fibers were desizing by acetone extraction for 6 hours, then treated with a 10% nitric acid solution at 50°C for 40 minutes, washed with water until neutral, and vacuum dried at 70°C for 6 hours. A 30 mmol / L Tris buffer solution was prepared and the pH was adjusted to 8.5. Dopamine hydrochloride was prepared into a 2.0 mg / mL solution and added to the carbon fibers at a liquid-to-solid ratio of 20 mL / g. The mixture was stirred at 25°C under air for 12 hours, washed, and vacuum dried at 60°C to constant weight, controlling the polydopamine loading to be 0.9 wt%.

[0028] S2. Add 20.83 g (0.100 mol) tetraethyl orthosilicate, 480 mL anhydrous ethanol, and 80 mL deionized water to the reaction vessel. Adjust the pH to 10.5 with ammonia and react at 32 °C for 2 h. Add 3.10 g (0.014 mol) 3-aminopropyltriethoxysilane and continue the reaction for 4.5 h. After centrifugation, washing with ethanol, and vacuum drying at 60 °C, amino-modified nano-silica with an average particle size of approximately 40–60 nm is obtained.

[0029] S3. Add 6.95 g (0.020 mol) hexachlorocyclotriphosphazene, 14.86 g (0.135 mol) hydroquinone, 19.91 g (0.144 mol) potassium carbonate and 300 mL N,N-dimethylformamide to the reaction flask, and react at 70 °C for 12 h under nitrogen protection; filter, concentrate under reduced pressure, precipitate in water, wash and dry under vacuum at 60 °C to obtain hexa(4-hydroxyphenoxy)cyclotriphosphazene.

[0030] S4. Prepare an aminated nano-silica dispersion of 6 mg / mL ethanol, add polydopamine-modified carbon fibers at a liquid-to-solid ratio of 20 mL / g, treat at 32℃ for 4 h, wash and dry, and control the loading of aminated nano-silica to 1.5 wt%. Then prepare a 6.5 mg / mL hexa(4-hydroxyphenoxy)cyclotriphosphazene ethanol / tetrahydrofuran mixed solution with a volume ratio of ethanol to tetrahydrofuran of 2.5:1, add carbon fibers at a liquid-to-solid ratio of 20 mL / g, treat at 40℃ for 5 h, wash and dry, and control the loading of hexa(4-hydroxyphenoxy)cyclotriphosphazene to 1.0 wt% to obtain the modified carbon fiber reinforcement.

[0031] S5. Take 52.5 parts by weight of bisphenol F type epoxy resin and 1.5 parts by weight of nano alumina, and disperse them at 70℃ and 1500 r / min for 30 min. After cooling to 48℃, add 37.5 parts by weight of methylhexahydrophthalic anhydride and 0.6 parts by weight of 2-ethyl-4-methylimidazolium, stir for 15 min and vacuum degas for 20 min. According to the ratio of 45 wt% modified carbon fiber reinforcement and 55 wt% resin matrix, vacuum impregnate at 55℃ and -0.092 MPa for 40 min. After lay-up, pre-press at 90℃ and 1.0 MPa for 30 min, heat to 130℃ and 3 MPa for 1.5 h, then heat to 165℃ and 4.5 MPa for 3 h, and then demold after cooling to below 60℃ at 2℃ / min.

[0032] Example 3: S1. PAN-based carbon fibers were desizing by acetone extraction for 8 hours, then treated with 15% nitric acid solution at 60°C for 60 minutes, washed with water until neutral, and vacuum dried at 80°C for 8 hours. A 50 mmol / L Tris buffer solution was prepared and the pH was adjusted to 8.8. Dopamine hydrochloride was prepared into a 3.0 mg / mL solution and added to the carbon fibers at a liquid-to-solid ratio of 25 mL / g. The mixture was stirred at 30°C under air atmosphere for 18 hours, washed, and vacuum dried at 70°C to constant weight, controlling the polydopamine loading to 1.5 wt%.

[0033] S2. Add 20.83 g (0.100 mol) tetraethyl orthosilicate, 560 mL anhydrous ethanol, and 70 mL deionized water to the reaction vessel. Adjust the pH to 11.5 with ammonia and react at 40 °C for 3 h. Add 4.43 g (0.020 mol) 3-aminopropyltriethoxysilane and continue the reaction for 6 h. After centrifugation, washing with ethanol, and vacuum drying at 70 °C, amino-modified nano-silica with an average particle size of approximately 60–80 nm is obtained.

[0034] S3. Add 6.95 g (0.020 mol) hexachlorocyclotriphosphazene, 15.86 g (0.144 mol) hydroquinone, 22.11 g (0.160 mol) potassium carbonate and 300 mL N,N-dimethylformamide to the reaction flask, and react at 80 °C for 16 h under nitrogen protection; filter, concentrate under reduced pressure, precipitate in water, wash and dry under vacuum at 70 °C to obtain hexa(4-hydroxyphenoxy)cyclotriphosphazene.

[0035] S4. Prepare an ethanol dispersion of 10 mg / mL aminated nano-silica, add polydopamine-modified carbon fibers at a liquid-to-solid ratio of 25 mL / g, treat at 40℃ for 6 h, wash and dry, and control the loading of aminated nano-silica to be 2.5 wt%. Then prepare an ethanol / tetrahydrofuran mixed solution of 8 mg / mL hexa(4-hydroxyphenoxy)cyclotriphosphazene with a volume ratio of 4:1, add carbon fibers at a liquid-to-solid ratio of 25 mL / g, treat at 50℃ for 8 h, wash and dry, and control the loading of hexa(4-hydroxyphenoxy)cyclotriphosphazene to be 1.8 wt%, to obtain the modified carbon fiber reinforcement.

[0036] S5. Take 60 parts by weight of bisphenol F type epoxy resin and 2 parts by weight of nano alumina, and disperse them at 80℃ and 2000r / min for 40min. After cooling to 55℃, add 45 parts by weight of methylhexahydrophthalic anhydride and 1.0 part by weight of 2-ethyl-4-methylimidazolium, stir for 20min and degas under vacuum for 30min. According to the ratio of 55wt% modified carbon fiber reinforcement and 45wt% resin matrix, vacuum impregnate at 65℃ and -0.098MPa for 60min. After lay-up, pre-press at 100℃ and 1.5MPa for 40min, heat to 140℃ and 4MPa for 2h, then heat to 175℃ and 6MPa for 4h, and then demold after cooling to below 60℃ at 3℃ / min.

[0037] Comparative Example 1 This comparative example is basically the same as Example 2, except that the carbon fiber is not modified with polydopamine, aminated nano-silica and hexa(4-hydroxyphenoxy)cyclotriphosphazene after desizing and nitric acid pretreatment, but is directly vacuum impregnated and gradient hot-pressed with the resin matrix of Example 2.

[0038] Comparative Example 2 This comparative example is basically the same as Example 2, except that only a polydopamine anchoring layer is formed on the carbon fiber surface, without loading aminated nano-silica and hexa(4-hydroxyphenoxy)cyclotriphosphazene.

[0039] Comparative Example 3 This comparative example is basically the same as Example 2, except that a polydopamine anchoring layer is formed on the carbon fiber surface and aminated nano-silica is loaded, but the interface assembly of hexa(4-hydroxyphenoxy)cyclotriphosphazene is not performed.

[0040] Comparative Example 4 This comparative example is basically the same as Example 2, except that hexa(4-hydroxyphenoxy)cyclotriphosphazene is directly assembled after the polydopamine anchoring layer is formed on the carbon fiber surface, without loading aminated nano-silica.

[0041] Comparative Example 5 This comparative example is basically the same as Example 2, except that a polydopamine anchoring layer is not formed on the surface of the pretreated carbon fiber. Instead, it is directly treated with a mixture of aminated nano-silica dispersion and hexa(4-hydroxyphenoxy)cyclotriphosphazene solution. The remaining steps and conditions are the same as in Example 2.

[0042] Comparative Example 6 This comparative example is basically the same as Example 2, except that the aminated nano-silica is replaced with non-aminated nano-silica with the same average particle size, and its loading is still controlled at 1.5 wt%. The remaining steps and conditions are the same as in Example 2.

[0043] To evaluate the overall performance of the modified carbon fiber-resin composite materials for automobiles obtained in Examples 1-3 and Comparative Examples 1-6, the following performance tests were conducted on each group of samples. The same sample preparation method and testing conditions were used for each group of samples. Five parallel samples were tested in each group, and the arithmetic mean of the test results was taken. 1. Tensile strength: Tested according to GB / T3354-2014 "Test method for tensile properties of oriented fiber reinforced polymer matrix composites", and the test results are expressed in MPa. 2. Bending strength: Tested according to GB / T3356-2014 "Test method for bending properties of oriented fiber reinforced polymer matrix composites", and the test results are expressed in MPa. 3. Interlaminar shear strength: Tested according to GB / T1450.1-2005 "Test method for interlaminar shear strength of fiber reinforced plastics", and the test results are expressed in MPa. 4. Impact toughness of simply supported beam: The test shall be conducted in accordance with GB / T1451-2005 "Test method for impact toughness of simply supported beam of fiber reinforced plastic", and the test results shall be expressed in kJ / m². 5. Limiting oxygen index: Tested in accordance with GB / T2406.2-2009 "Determination of flammability by oxygen index method for plastics - Part 2: Room temperature test", and the test results are expressed as %. 6. Load deformation temperature: The test shall be conducted in accordance with GB / T1634.2-2019 "Determination of load deformation temperature of plastics - Part 2: Plastics and hard rubber", and the test results shall be expressed in °C.

[0044] Table 1: Performance Tests

[0045] As can be seen from the test results in Table 1, the tensile strength, flexural strength, interlaminar shear strength and impact toughness of Example 2 reached 769 MPa, 936 MPa, 64.2 MPa and 87.3 kJ / m², respectively, while the limiting oxygen index and load deformation temperature reached 28.5% and 170℃, respectively. Compared to Example 2, Comparative Example 1, which did not construct the polydopamine, aminated nano-silica, and hexa(4-hydroxyphenoxy)cyclotriphosphazene interfacial layer on the carbon fiber, exhibited reduced tensile strength, flexural strength, interlaminar shear strength, and impact toughness to 641 MPa, 776 MPa, 47.9 MPa, and 66.8 kJ / m², respectively, with a limiting oxygen index of only 22.8%. This indicates that multi-level interfacial modification plays a crucial role in improving the interfacial bonding between carbon fiber and the resin matrix, as well as the overall performance of the composite material. Comparative Example 2, with only a polydopamine anchoring layer, showed improved mechanical properties compared to Comparative Example 1, but still significantly lower than the examples. This suggests that polydopamine primarily serves as an interfacial activator and anchoring agent, and further integration with nano-reinforcing phases and phosphorus and nitrogen functional components is still necessary. Comparative Example 3, which included polydopamine and aminated nano-silica but omitted hexa(4-hydroxyphenoxy)cyclotriphosphazene, achieved a tensile strength of 735 MPa and an interlaminar shear strength of 59.6 MPa, but a limiting oxygen index of only 24.4%. This indicates that aminated nano-silica can effectively improve interfacial load transfer capacity, and the phosphorus-nitrogen-containing cyclotriphosphazene interfacial layer plays an important role in improving the flame retardant properties of the material. Comparative Example 4, which retained polydopamine and hexa(4-hydroxyphenoxy)cyclotriphosphazene but omitted aminated nano-silica, still achieved a limiting oxygen index of 27.3%, but its interlaminar shear strength and impact toughness decreased to 56.2 MPa and 77.3 kJ / m², respectively. This further demonstrates that the nano-rough structure and multi-point interfacial interaction formed by aminated nano-silica are beneficial for improving interfacial bonding and mechanical properties. Furthermore, Comparative Example 5, which directly treated carbon fibers with aminated nano-silica and hexa(4-hydroxyphenoxy)cyclotriphosphazene without constructing a polydopamine anchoring layer, showed significantly lower performance than the examples, indicating that the polydopamine anchoring layer plays a crucial role in the stable loading of subsequent functional components and the formation of multi-level interfacial structures. Comparative Example 6, using unaminated nano-silica, exhibited lower tensile strength, interlaminar shear strength, and impact toughness than the examples, suggesting that the amino functionalization of the nano-silica surface enhances the interaction between nanoparticles, the polydopamine interfacial layer, and the resin matrix. In summary, the polydopamine anchoring layer, the aminated nano-silica reinforcing layer, and the hexa(4-hydroxyphenoxy)cyclotriphosphazene interfacial layer respectively provide interfacial anchoring, nano-reinforcement, and phosphorus-nitrogen flame retardancy. The combination of these three elements can improve the interfacial bonding performance of carbon fibers / resin while simultaneously maintaining the mechanical properties, flame retardancy, and heat resistance of the composite material.

[0046] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0047] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

[0048] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.

Claims

1. A modified carbon fiber-resin composite material for automobiles, characterized in that, It is formed by composite curing of modified carbon fiber reinforcement and resin matrix, wherein the modified carbon fiber reinforcement accounts for 35-55 wt% of the total mass of the composite material, and the resin matrix accounts for 45-65 wt% of the total mass of the composite material, with the two totaling 100 wt%. The modified carbon fiber reinforcement is obtained by sequentially forming a polydopamine anchoring layer, an aminated nano-silica reinforcement layer, and a phosphorus-nitrogen-containing triphosphazene interface layer on the surface of carbon fiber. Based on the mass of unmodified carbon fiber, the loading of polydopamine is 0.3–1.5 wt%, the loading of aminated nano-silica is 0.5–2.5 wt%, and the loading of phosphorus-nitrogen-containing cyclic triphosphazene compound is 0.3–1.8 wt%; the phosphorus-nitrogen-containing cyclic triphosphazene compound is hexa(4-hydroxyphenoxy)cyclic triphosphazene. The resin matrix is ​​composed of the following raw materials in parts by weight: 45-60 parts of bisphenol F type epoxy resin, 30-45 parts of methyl hexahydrophthalic anhydride, 0.3-1.0 parts of 2-ethyl-4-methylimidazolium, and 1-2 parts of nano-alumina.

2. The modified carbon fiber-resin composite material for automobiles according to claim 1, characterized in that, The carbon fiber is PAN-based carbon fiber with a single filament diameter of 5-8 μm. Before the interface modification, the carbon fiber is extracted with acetone for 4-8 hours to remove the original sizing agent, then treated with a nitric acid solution with a mass concentration of 5-15% at 40-60℃ for 20-60 minutes, then washed with deionized water until neutral, and then vacuum dried at 60-80℃ for 4-8 hours.

3. The modified carbon fiber-resin composite material for automobiles according to claim 1, characterized in that, The polydopamine anchoring layer is formed as follows: pretreated carbon fibers are added to a dopamine hydrochloride solution with a concentration of 1.0–3.0 mg / mL. The dopamine hydrochloride solution is prepared using a Tris buffer solution with a concentration of 10–50 mmol / L and the pH is adjusted to 8.2–8.

8. The mixture is stirred and reacted at 20–30°C in air for 6–18 hours to allow dopamine to oxidize and polymerize in situ on the carbon fiber surface. After the reaction is completed, the carbon fibers are washed with deionized water and vacuum dried at 50–70°C to obtain polydopamine-modified carbon fibers.

4. The modified carbon fiber-resin composite material for automobiles according to claim 1, characterized in that, The aminated nano-silica was prepared using tetraethyl orthosilicate and 3-aminopropyltriethoxysilane, wherein the molar ratio of tetraethyl orthosilicate to 3-aminopropyltriethoxysilane was 1:0.08–0.

20. Specifically, tetraethyl orthosilicate was added to a mixed solvent consisting of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 4–8:

1. Ammonia was added to adjust the pH of the system to 9.5–11.

5. After stirring and reacting at 25–40°C for 1–3 hours, 3-aminopropyltriethoxysilane was added, and the reaction was continued for 3–6 hours. After centrifugation, washing with ethanol, and vacuum drying at 50–70°C, aminated nano-silica with an average particle size of 20–80 nm was obtained.

5. The modified carbon fiber-resin composite material for automobiles according to claim 1, characterized in that, The phosphorus-containing nitrogen-containing cyclic triphosphazene compound is prepared by the following method: hexachlorocyclotriphosphazene, hydroquinone, and an acid-binding agent are added to an organic solvent, wherein the molar ratio of hexachlorocyclotriphosphazene to hydroquinone is 1:6.3-7.2, and the molar ratio of hexachlorocyclotriphosphazene to the acid-binding agent is 1:6.5-8.0; the reaction is carried out under nitrogen protection at 60-80℃ for 8-16 h; after the reaction is completed, the solid salt is removed by filtration, most of the solvent is removed by vacuum, the concentrated solution is added to deionized water to precipitate the solid, washed with water, and dried under vacuum at 50-70℃ to obtain hexa(4-hydroxyphenoxy)cyclotriphosphazene; the acid-binding agent is potassium carbonate, and the organic solvent is N,N-dimethylformamide.

6. The modified carbon fiber-resin composite material for automobiles according to claim 1, characterized in that, The modified carbon fiber reinforcement is prepared by the following method: polydopamine-modified carbon fibers are added to an aminated nano-silica ethanol dispersion with a concentration of 2-10 mg / mL, stirred at 25-40℃ for 2-6 h, washed and dried, and then added to a hexa(4-hydroxyphenoxy)cyclotriphosphazene ethanol / tetrahydrofuran mixed solution with a concentration of 5-8 mg / mL, and assembled at 30-50℃ for 2-8 h. The volume ratio of ethanol to tetrahydrofuran is 1:1 to 4:

1. After washing and drying, the modified carbon fiber reinforcement is obtained.

7. A method for preparing a modified carbon fiber-resin composite material for automobiles according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Desizing and oxidation pretreatment are performed on the carbon fiber to form a polydopamine anchoring layer on the surface of the carbon fiber, thereby obtaining polydopamine modified carbon fiber. S2. Aminated nano-silica is loaded onto the surface of the polydopamine-modified carbon fiber, and then hexa(4-hydroxyphenoxy)cyclotriphosphazene is loaded to obtain the modified carbon fiber reinforcement. S3. Weigh 45-60 parts of bisphenol F type epoxy resin and 1-2 parts of nano alumina according to the weight ratio, disperse them at 1000-2000 r / min for 20-40 min at 60-80℃, cool them to 40-55℃, add 30-45 parts of methylhexahydrophthalic anhydride and 0.3-1.0 parts of 2-ethyl-4-methylimidazolium, stir evenly, and then degas under vacuum for 10-30 min to obtain the resin matrix; S4. Vacuum impregnate the modified carbon fiber reinforcement obtained in step S2 with the resin matrix obtained in step S3, such that the modified carbon fiber reinforcement accounts for 35-55 wt% of the total mass of the composite material, the resin matrix accounts for 45-65 wt%, and the total of the two is 100 wt%, to obtain a prepreg. S5. After the prepreg is laid up, it is hot-pressed and cured, cooled and demolded to obtain a modified carbon fiber-resin composite material for automobiles.

8. The preparation method according to claim 7, characterized in that, In step S4, the impregnation temperature is 45-65℃, the vacuum degree is -0.085--0.098MPa, and the impregnation time is 20-60min; the resin content in the prepreg is 45-65wt%.

9. The preparation method according to claim 7, characterized in that, Step S5 adopts a gradient hot-press curing process, specifically: first, pre-press for 20-40 minutes at 80-100℃ and 0.5-1.5MPa, then heat to 120-140℃ and 2-4MPa for 1-2 hours, then heat to 155-175℃ and 3-6MPa for 2-4 hours; after curing, cool to below 60℃ at a cooling rate of 1-3℃ / min before demolding.